The influence of implant surface properties on cell adhesion and proliferation - Pessková, V; Kubies, D; Hulejová, H; Himmlová, L (Journal of materials science. Materials in medicine, 2007)
Interactions of the foreign material of implant and the living tissue on the cell level can cause prolonged healing or, worse, loss of the implant. The cell response to the presence of some implant materials was studied under in vitro conditions. The influence of physicochemical surface parameters on the response of the cells in the immediate vicinity of implants, namely on adhesion, proliferation and synthetic activity of fibroblasts, and on the blood coagulation were compared. The direct contact of tested materials (titanium and Ti6Al4V alloy with various surface treatments, Cr Co Mo alloy, hydroxyapatite-coated titanium, zirconium oxide ceramics, polyethylene and carbon composite) on cell spreading was monitored and the presence of TNF-alpha and IL-8 was evaluated in the cultivation medium. The formation of blood clots was investigated on samples immersed in a well with freshly drawn whole rabbit blood using a scanning electron microscope. The surface free energy was estimated using the measurement of static contact angle. Both the advancing and receding contact angles were measured by the dynamic Wilhemy plate method. Two main groups with extremes in cell viability were established. In the first group the increased polar component of surface free energy, the highest cell density, the lowest inflammatory cytokine production, but no fibres in the clotting blood were found. On the contrary, the second group of materials with a very low polar component of the surface free energy showed distinctly higher expression of inflammatory mediators, low cell proliferation, but faster formation of fibres in the blood coagulum.
Keywords: biokompatibilní potahované materiály; techniky in vitro; Humans; experimentální implantáty; povrchové vlastnosti; testování materiálů; Interleukin-8; interleukin-8; Cell Adhesion; lidé; zvířata; proliferace buněk; Cells, Cultured; hemokoagulace; TNF-alfa; Coated Materials, Biocompatible; Blood Coagulation; kultivované buňky; Cell Proliferation; In Vitro Techniques; králíci; Tumor Necrosis Factor-alpha; fibroblasty; Animals; buněčná adheze; Implants, Experimental; Rabbits; Surface Properties; Fibroblasts; Materials Testing